Analisis Bakteri E. Coli Minuman Es Dawet di Kabupaten Kudus - David Laksamana Caesar; Umi Rohmah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
The coverage of drinking water quality inspection in Central Java has only reached 82.1%. One type of drinking water that is often consumed by the public is dawet ice. Dawet ice can be contaminated by pathogenic bacteria, one of which is Escherichia coli (E. coli). Contamination can occur through water used to process coconut milk or from water used to make ice. In addition, contamination can occur during the processing or distribution process of dawet ice with. This study aims to determine the presence of E. coli bacteria in dawet ice drinks. This type of research uses quantitative descriptive analysis instrument with the Plate Count Agar (PCA) method. Samples taken amounted to 30 samples in the area of Kudus Regency. The results showed that the presence of E. coli bacteria in dawet ice samples sold in Kudus Regency. There are still many dawet ice in Kudus Regency which contain E.coli bacteria, namely 83.4%. This is because respondents do not pay attention to personal hygiene and sanitation